Pentingnya Pengembangan Kompetensi Guru (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2018)
The development of science and technology has led to changes and competition for various circles, organizations, companies, even the world of education. Therefore, Human Resources that is needed today is Human Resources who are able to master the technology quickly, adaptive, and responsive to technological changes. In this condition, personal integrity is increasingly important to win the competition.To respond to the demands and challenges that exist, organizations, corporations and educational institutions must prepare reliable workers in various fields. It is because Human Resources is a resource that is needed by an organization or educational institution, because Human Resources is a source that plays an active role on the way an organization and decision-making process. In the world of education, of course, is the teacher as an educator. Teachers play a major role in the development of education and as the most influential component of the creation of quality educational activities and results. Therefore, teachers need to give education, training, development and experience sufficient to improve their quality, so that they can carry out their duties and responsibilities. Responsibility will be accomplished if supported by ability. The ability to produce achievement and achievement will determine the quality of education. Finally training and development is a basic need that is expected to be influential in improving teacher competence and achievement.